AUTOMATIC ABSTRACTING OF TEXTUAL INFORMATION BASED ON SITUATIONAL LINKS MODELING OF APPLICATION DOMAIN CONCEPTS - L. V. Stepura (Informatika)
A model of abstracting textual information, based on the formalization of information languages by a special generative grammar and the concepts of word self-descriptiveness and contextual links between words, is considered. A method of abstracts synthesis for textual documents by identifying informative sentences, constructing their context and generating chains of syntax trees is suggested.